The prognostic value of cytogenetic markers for early diagnosis of colorectal cancer - Lozynska, M. (Experimental Oncology, 2009)
To investigate the spectrum of chromosome changes in colorectal adenomas and adenocarcinomas and to evaluate the prognostic significance of the chromosome rearrangements. Methods: The study was carried out using the cytogenetic analysis of biopsy specimens (n = 56) of single and multiply adenomas (familial adenomatous syndromes; n = 38) and adenocarcinomas (n = 18). Results: The karyotype of adenomas was normal in the majority of cases, but some adenomas with severe dysplasia of epithelium carry the quantitative chromosome abnormalities and structural rearrangements. The combination of additional copies of chromosomes 13, 18, 20 in adenomas points on an unfavorable prognosis. The chromosome abnormalities were found in 100% of adenocarcinomas biopsy specimens. Conclusions: The transition from colorectal adenomas to adenocarcinomas is accompanied by elevation of chromosome abnormalities level, in particular, by increased clonal variety, selective accumulation of the copies of chromosomes 2, 3, 20, 16, with simultaneous monosomy of chromosomes 17, 18, 8, 6, 14, and del 1p.